Proposing late transition metal complexes as frustrated Lewis pairs - a computational investigation - Pal, Amrita; Vanka, Kumar (Dalton Transactions, 2013)
There has been considerable interest in recent times to develop transition metal complex systems that can demonstrate metal-ligand cooperativity. It has recently been shown (Wass et al., J. Am. Chem. Soc., 2011, 133, 18463) that early transition metals can cooperate with ligands carrying phosphines as pendant groups, working as metal analogues to frustrated Lewis pairs (FLPs) to mediate in a variety of important reactions. What the current work attempts to do is to show how this concept of metal containing FLPs can be expanded to include late transition metal complexes as well: complexes that have been modified from existing systems that serve as efficient catalysts for homogeneous polymerization. A modified palladium complex has been considered in this regard as an example of a potential late transition metal FLP and studied with full quantum mechanical calculations. The calculations indicate that this complex would be effective at catalyzing ammonia borane dehydrogenation. The possibility of competing side reactions such as reductive elimination have also been considered, and it has been found that such processes would also yield stable products which could act as an FLP in catalyzing reactions such as the dehydrogenation of ammonia borane. The current work therefore expands the scope of metal containing FLPs to include late transition metals and demonstrates computationally the potential of such complexes for exhibiting metal-ligand cooperativity.

Proposing efficient new pendant group polymer electrolyte membranes for fuel cells: a computational study - Mane, Manoj V.; Vanka, Kumar (Journal of Physical Chemistry C, 2014)
There is a need to develop new membranes for fuel cells that can conduct protons with high efficiency and at high temperatures. This paper reports a theoretical study of proton transfer barriers in newly proposed polymer electrolyte membranes (PEMs), having pendant nitrogen containing crown ether groups on an alkyl backbone. The proton transfer in the proposed pendant group PEMs would occur without the need of an external agent such as water or phosphoric acid, and without the need for the pendant groups to rotate and reorient themselves after each proton transfer. The current study shows that this would make the proposed PEMs very efficient, with low proton transfer barriers. This has been seen to be true for a range of different PEM cases considered, differing in the number of linker atoms in the alkyl backbone and in the number of nitrogens contained in each pendant group, thus, indicating the potential of the proposed structures as PEMs for fuel cells.

Porous porphyrin organic polymer (PPOP) for visible light triggered hydrogen production - Mukherjee, Gargi; Thote, Jayshri; Aiyappa, Harshitha Barike; Kandambeth, Sharath; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
A visible light active porphyrin-based porous organic polymer having high chemical stability and surface area has been synthesized and its ability to influence the photocatalytic activity of large band gap-TiO2 nanoparticles has been tested. The resultant composite shows improved photocatalytic activity as compared to the parent precursors. This study provides insights into the photosensitizing ability of the polymer in addition to its ability to firmly harbor nanoparticles onto its surface.

p-Selective (sp(2))-C-H functionalization for an acylation/alkylation reaction using organic photoredox catalysis - Pandey, Ganesh; Tiwari, Sandip Kumar; Singh, Bhawana; Vanka, Kumar; Jain, Shailja (Chemical Communications, 2017)
p-Selective (sp(2))-C-H functionalization of electron rich arenes has been achieved for acylation and alkylation reactions, respectively, with acyl/alkylselenides by organic photoredox catalysis involving an interesting mechanistic pathway.

Phosphite mediated asymmetric N to C migration for the synthesis of chiral heterocycles from primary amines - Rani, Soniya; Dash, Soumya Ranjan; Bera, Asish; Alam, Md Nirshad; Vanka, Kumar; Maity, Pradip (Chemical Science, 2021)
A phosphite mediated stereoretentive C-H alkylation of N-alkylpyridinium salts derived from chiral primary amines was achieved. The reaction proceeds through the activation of the N-alkylpyridinium salt substrate with a nucleophilic phosphite catalyst, followed by a base mediated [1,2] aza-Wittig rearrangement and subsequent catalyst dissociation for an overall N to C-2 alkyl migration. The scope and degree of stereoretention were studied, and both experimental and theoretical investigations were performed to support an unprecedented aza-Wittig rearrangement-rearomatization sequence. A catalytic enantioselective version starting with racemic starting material and chiral phosphite catalyst was also established following our understanding of the stereoretentive process. This method provides efficient access to tertiary and quaternary stereogenic centers in pyridine systems, which are prevalent in drugs, bioactive natural products, chiral ligands, and catalysts.

Polymorphs of green fluorescence protein chromophore analogue: fluorescence switching with thermal stimuli - Mali, Bhupendra P.; Dash, Soumya Ranjan; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2022)
Polymorphs of fluorescent organic materials offer significant implications in optoelectronics and advanced materials as they modulate photoluminescence properties. A slight alteration in the conformation/packing of molecules in the crystals shows variation in photoluminescence. This necessitates the polymorph screening of these materials to develop novel crystalline forms with distinct fluorescence emissions for broader application. In continuation of our work on the polymorph screening of Green Fluorescence Protein Chromophore (GFPc), we have synthesized a new imidazoline derivative, ethyl (Z)-2-(2-methyl-5-oxo-4-(3,4,5-trimethoxybenzylidene)-4,5-dihydro-1H-imi dazol-1- yl)acetate (1). Polymorph screening of 1 under different crystallization conditions revealed three polymorphs, Form I (needle), Form II (block), and Form III (polycrystalline material). Forms I and II are the outcome of solution crystallization, whereas Form III was produced from the melt crystallization of Forms I and II. DSC, HSM, and powder and single-crystal XRD studies indicate the conversion of Form I and Form III crystals to Form II crystals on thermal stimuli. The photoluminescence studies revealed cyan, yellow, and yellowish-green fluorescence emission for Forms I, II, and III crystals, respectively. The difference in photoluminescence could be due to the variance in aggregation modes like H-aggregation in Form I and J-aggregation in Form II crystals. Form I, Form II, and Form III crystals also showed irreversible thermal fluorescent switching from cyan-yellow-green due to polymorphic phase transitions. The study correlates the direct observation of the modulation of the excited-state transition under thermal stimuli in the crystalline phase. It will help augment the pace in the research of thermally responsive fluorescent materials.

Predicting the redox potentials of phenazine derivatives using DFT-assisted machine learning - Ghule, Siddharth; Dash, Soumya Ranjan; Bagchi, Sayan; Joshi, Kavita; Vanka, Kumar (ACS Omega, 2022)
This study investigates four machine-learning (ML) models to predict the redox potentials of phenazine derivatives in dimethoxyethane using density functional theory (DFT). A small data set of 151 phenazine derivatives having only one type of functional group per molecule (20 unique groups) was used for the training. Prediction accuracy was improved by a combined strategy of feature selection and hyperparameter optimization, using the external validation set. Models were evaluated on the external test set containing new functional groups and diverse molecular structures. High prediction accuracies of R2 > 0.74 were obtained on the external test set. Despite being trained on the molecules with a single type of functional group, models were able to predict the redox potentials of derivatives containing multiple and different types of functional groups with good accuracies (R2 > 0.7). This type of performance for predicting redox potential from such a small and simple data set of phenazine derivatives has never been reported before. Redox flow batteries (RFBs) are emerging as promising candidates for energy storage systems. However, new green and efficient materials are required for their widespread usage. We believe that the hybrid DFT-ML approach demonstrated in this report would help in accelerating the virtual screening of phenazine derivatives, thus saving computational and experimental costs. Using this approach, we have identified promising phenazine derivatives for green energy storage systems such as RFBs.

Pd nanoparticles supported on N-incorporated hybrid organosilica as an active and selective low-temperature phenol hydrogenation catalyst - Betsy, K. J.; Bajpai, Priyam; Lazar, Anish; Vanka, Kumar; Vinod, C. P. (ACS Applied Nano Materials, 2023)
A heterogeneous Pd-NPMO hybrid-silicacatalyst is synthesized andits application for aqueous phase selective hydrogenation of phenolto cyclohexanone at near ambient temperature (40 degrees C) and underatmospheric hydrogen pressure is demonstrated. The homogeneously distributedPd nanoparticles on N-bridged hybrid mesoporous organosilica showedremarkable activity and selectivity for cyclohexanone compared tothe unmodified Pd-SBA-15 catalyst. Control experiments strongly claimthe role of nitrogen domains in the organic framework of hybrid silicasupport in stabilizing small Pd nanoparticles and possibly modifyingthe Pd sites responsible for catalysis to activate the substrate moleculesin water. The hybrid silica catalyst was stable and reused severaltimes without any significant drop-in activity, proving the heterogeneityof the bifunctional Pd catalyst. Based on the density functional theorystudy and experimental interventions, a possible reaction mechanismfor the low-temperature phenol hydrogenation explaining the role oforganic domains in the hybrid-silica framework is proposed.
Keywords: cyclohexanone; Hybrid silica; palladium nanoparticles; Periodic mesoporous organosilica; phenol hydrogenation

Potential role of lewis acid-base adducts in enhancing stereoselectivity in ziegler-natta catalysts: a DFT study - Raj, K. Vipin; Gupta, Virendra Kumar; Vanka, Kumar (Journal of Physical Chemistry C, 2023)
Ziegler-Natta (Z-N) systems have been well established as heterogeneous catalysts that produce isotactic polypropylene and polyethylene with great efficiency. Such systems benefit considerably from donors (Lewis bases), whose addition significantly improves the stereoselectivity of polymerization. There is a consensus that the primary role of the external donors is to coordinate at the vacant site created by the extraction of internal donors and thus maintain the stereoselectivity. However, the bite difference between internal donors such as phthalates or succinate derivatives and external donors such as alkoxysilanes raises the question of how external donors can effectively replace internal donors. In order to investigate this, we have chosen four external alkoxysilane donors: (1) diisopropyl dimethoxysilane, (2) dicyclopentyl dimethoxysilane, (3) disec-butyl dimethoxysilane, and (4) sec-butyl(methyl) dimethoxysilane. DFT studies reveal that the bite difference problem can be overcome by the favorable formation of adducts between the alkoxysilane external donors and AlEt2Cl in the Z-N systems. These adducts tend to coordinate in the vicinity of the active site. Furthermore, our findings demonstrate the potential of these Lewis acid-base adducts to enhance the stereoselectivity of Z-N catalysts significantly.

Pair of dinuclear Fe(II) enantiomers: syntheses and structures of ΛΔ/ΔΛ-Bis(Dihydridoborate) complexes - Kaur, Urminder; Gayen, Sourav; Sharma, Himanshu; Vanka, Kumar; Ghosh, Sundargopal (CHEMISTRY-A EUROPEAN JOURNAL, 2025)
In our effort to establish a direct synthetic approach for bis(dihydridoborate) complexes of first-row transition metals, we have investigated the reactivity of [Cp*Fe(dppe)Cl] (dppe =1,2-bis(diphenylphosphino)ethane) with Na[BH3L] (L =2-mercaptopyridine (mp) and 2-mercaptobenzothiazole (mbz)) that led to the formation of iron(II) dihydridoborate complexes, [Cp*Fe{kappa 3-S,H,H-(H2BH(L))}] 1 a-b (L=mp (1 a) and L=mbz (1 b)). Further, in an attempt to isolate the bis(dihydridoborate) complex of iron by the insertion of borane into the kappa 2-N,S-chelated iron complex, [(dppe)Fe{kappa 2-N,S-(mp)}2] (2), we have isolated and structurally characterized a rare example of dimeric iron bis(dihydridoborate) complex, [Fe{kappa 3-S,H,H-(H2BH(mp))}2]2, Lambda Delta/Delta Lambda-3 as pair of enantiomers. Interestingly, these enantiomers Lambda Delta/Delta Lambda-3 have two trans-[Fe{kappa 3-S,H,H-(H2BH(mp))}2] moieties bridged through sulfur atoms of 2-mercaptopyridinyl ligands, where the iron centres are hepta-coordinated. The natural bond-orbital (NBO) analyses of Lambda Delta-3 and Delta Lambda-3 show considerable electron donation from the filled sigma B-H bonding orbital to vacant dz2 \${{d}_{{z}<\^>{2}}}\$ orbital of iron with a substantial contribution from the hydrogen atoms. The localized orbital bonding analysis (LOBA) method suggests that all the iron centres are in +2 oxidation state.
Keywords: B-H activation; Bis(dihydridoborate); Enantiomer; Heptacoordinate; iron

Palladium(II)-catalyzed desymmetrization of 2-alkynylbenzoate-tethered cyclohexadienones for the synthesis of polycyclic compounds - Rai, Archana; Bajpai, Priyam; Gamidi, Rama Krishna; Vanka, Kumar; Das, Utpal (Organic Letters, 2025)
Pd-catalyzed cascade cyclization of 2-alkynylbenzoate-tethered cyclohexadienone was developed for the single step synthesis of isocoumarin-fused dihydrochromenones. This highly atom economical method proceeds via 6-endo-dig cyclization of tert-butyl benzoate with a tethered alkyne. By modulating the reaction solvent and metal catalyst, the methodology was diverted for the purposeful synthesis of either of the E/Z tetra-substituted alkenes.

Pushing the boundaries of pnictogen-bonding organocatalysis: a clash of Sb(III) versus Bi(III) - Sharma, Jyoti; Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2025)
The sigma-hole-mediated noncovalent organocatalysis involving the pnictogen (Pn) elements has thus far been explored mostly from nitrogen to antimony, with antimony identified as the most effective catalyst. Herein, density functional theory calculations have been carried out to demonstrate that tri-aryl (Ar)-substituted bismuth(III) complexes can outperform their antimony counterparts in both anion (Cl-) binding and catalytic activity. Using a range of computational methods, a good correlation between the sigma-hole strength, chloride binding affinity, and the reaction barrier is established. Notably, the findings reveal that dispersion interactions are the dominant force in catalysts with weaker sigma-holes, while electrostatic interactions prevail in catalysts with stronger sigma-holes (for the anion abstraction step). In all cases, Bi(III) catalysts emerge as the winner over the Sb(III) analogues. Additionally, beyond the primary Pn. . .Cl interactions, several secondary interactions such as Cl. . .H/F-C(Ar) and Cl-. . . H-C(Si-TBS) also play a significant role in stabilizing the transition states.
Keywords: Antimony; Bismuth; organocatalysis; pnictogen; sigma (sigma) holes

Photoluminescence decay lifetime study of hydrothermally synthesized highly porous ruthenium-silica composite for optical dissolved oxygen sensing application - Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Pandya, Rinu; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Vanka, Kumar; Saha, Avishek; Kanawade, Rajesh (ACS Applied Nano Materials, 2026)
Pore size and surface area of photoluminescence (PL)-based transition metal composites play crucial roles in facilitating oxygen diffusion, thereby enhancing the response and sensitivity of optical dissolved oxygen (DO) sensors. In this study, we successfully applied the hydrothermal method to synthesize a porous ruthenium composite embedded in a silica matrix, demonstrating its effectiveness for optical DO sensing applications. The ruthenium-silica (Ru-Si) composites were synthesized using Ru(bpy)3 2+ and tetraethyl orthosilicate (TEOS) as precursors, with reaction temperatures ranging from 120 degrees C to 200 degrees C over a fixed duration of 4 h. The structural, morphological, and compositional characterization techniques confirmed the successful synthesis and evaluated the porosity, surface features, and chemical structure of the resulting composites. The optimized Ru-Si composite exhibited the highest porosity, characterized by a specific surface area of 996.78 m2 g- 1, and exhibited the highest decay lifetime of 8.14 mu s in deionized (DI) water, compared to other composites. Importantly, we demonstrate an excellent linear response of the synthesized Ru-Si composite to DO concentrations ranging from 2.58 to 11.16 mg L-1, with a Stern-Volmer constant of 0.12. Furthermore, a density functional theory study was conducted to investigate the electronic transitions and to elucidate the oxygen quenching mechanism of the excited Ru composite with molecular oxygen. The calculated photophysical parameters of the composite show good agreement with the experimental results. Preliminary results suggest that the synthesized Ru-Si with high pore size and surface area could be an efficient and effective composite for use in DO sensing applications.
Keywords: Hydrothermal method; opticalDO sensor; oxygen quenching; photoluminescent; ruthenium composite